Focus on family functioning in anorexia nervosa: new perspectives using the Lausanne Trilogue Play. (June 2020) - Mensi, Martina Maria; Balottin, Laura; Rogantini, Chiara; Orlandi, Marika; Galvani, Marta; Figini, Silvia; Chiappedi, Matteo; Balottin, Umberto
Highlights: Families of adolescents affected by AN show dysfunctional alliances in LTPc. AN families have a worse family functioning than comparison group. Participation and Organization scores are lower in AN families. AN group have lower scores in third and fourth LTPc phases than comparison group. LTPc may predict the possibility of belonging to a family with a daughter with AN. Abstract: 31 families of female adolescents affected by anorexia nervosa (AN) and 20 of girls with emotional and behavioral disorders participated in a semi-standardized videotaped game: the Lausanne Trilogue Play (LTPc). We aimed to clarify if there is a typical AN family profile and if the LTPc procedure could predict the risk of developing AN. We confirmed that AN families exhibit dysfunctional alliances. Particularly because of the difficulty of the three members to be available to the interaction at least with their body (participation) and to comply with the role expected at each stage of the game (organization). Moreover, these families show a significant worse functioning, especially regards to the mother-daughter phase of the game, in focal attention and affective contact functional levels, while in triadic and couple phases they present lower scores than comparison group in all functional levels. Furthermore, we found that LTPc may predict the possibility of belonging to a family with a daughter with AN rather than one whose daughter has a different disorder. Therefore, LTPc would allow clinicians foresee the risk of developing AN and tailoring the most suitable therapeutic intervention and finally see its effectiveness using LTPc for later follow-up video feedback sessions.